The characteristics of temper outbursts in Prader–Willi syndrome. Issue 11 (5th October 2018) - Rice, Lauren J.; Woodcock, Kate; Einfeld, Stewart L.
Abstract : The purpose of this study was to develop a comprehensive understanding of temper outbursts in Prader–Willi syndrome (PWS). A survey was developed from interviews conducted with individuals with PWS and their caregivers. The survey was completed by 101 primary caregivers. The findings suggest that outburst frequency decreases with age while duration increases. Adolescents exhibited more severe behaviors than children or adults. No differences were found across gender or genetic subtype. Provocations fit into three themes: goal blockage, social injustice, and difficulty dealing with change. Distracting the person or giving them space to calm down were the only management strategies judged effective. Risperidone, sertraline, and fluoxetine were the most common medications prescribed for outbursts, though parents reported only minor effects.